ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING DAN PENENTUAN HARGA JUAL DENGAN PENDEKATAN COST PLUS PRICING - Leo, Leo Deby Eko Saputra; Ayudyah Eka Apsari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The purpose of this study was to evaluate the method used to calculate the selling price and production costs at MSMEs Bakpia 803 Bu Marno. Proper calculation of production costs helps to establish the right selling price to achieve the best level of profit. The company's primary Data used in this study, using a quantitative descriptive approach. The findings showed that the MSME method Bakpia 803 Bu Marno produce production costs of Rp 624/pcs, while the method of full costing produce production costs of Rp 676 / pcs. In the calculation of production costs, MSMEs Bakpia 803 Bu Marno ignored the depreciation costs of equipment and buildings. Bakpia 803 UMKM Bu Marno calculated a total production cost of Rp6, 988, 000. While the full costing method is Rp7, 576, 713. With the company's method, the selling price per box containing 20 bakpia is Rp 25,000, with a profit margin of about 55%. On the other hand, with the method of cost plus pricing the calculated selling price is Rp 19,960 per box containing 20 bakpia.